The properties of medium density fibreboard manufactured from rubberwood branches - Mohd Nor Mohd Yusoff (In : Management for enhanced profitability in plantations : Proceedings of the 1994 International Planters Conference, Kuala Lumpur, 1994; p433-440)
The MDF industry in Malaysia is expanding rapidly due to the countrys booming economy and the world demand for MDF. Since rubberwood is the principle raw material for composite products as well as furniture, certain localities in Peninsular Malaysia are expected to experience shortage of rubberwood supply. However, during the replanting of rubber trees, there is quite a substantial amount of wood from the small diameter branches left on the grround. A study was conducted to evaluate the use of small diameter rubberwood branches for MDF manufacture and also the effect of bark on board qualities. Chipping of the rubberwood branches was carried using the portable chipper brought to the plantation. Screened rubberwood chips of specific dimensions were used to prepare fibres in the pressurised refiner. In the manufacture of MDF, a weighed quantity of dry fibres was blended with 10 per cent urea formaldehyde resin and 1 per cent wax emulsion. The prepressed board was consolidated at 190 C with an initial pressure of 80 kg cm -2 for 4 min. The board density was fixed at 700 kg m-3. The boards produced were tested for their strengths and dimensional stabilities according to the Japanese Industrial Standard. The resulted indicated that the samples without bark produced boards with higher strength properties and lower thickness swelling than those samples containing bark. The presence of bark was expected to increase the consumption of resin in the boards, thereby reducing the bonding between fibres. It was also noted that those samples without bark exhibited increased strength properties and dimensional stability with increasing diameter of branches. On the other hand, MDF from samples containing bark seemed to produce decreasing strength properties with increasing diameter of branches as the larger diameter branches contain more bark which impaired the board properties.
Keywords: Fibreboard; Rubberwood